2013
DOI: 10.1007/s10120-013-0265-7
|View full text |Cite
|
Sign up to set email alerts
|

Can we apply the same indication of endoscopic submucosal dissection for primary gastric cancer to remnant gastric cancer?

Abstract: Background Currently, remnant gastric cancer (RGC) is uncommon compared with gastric stump cancer, but early detection of gastric cancer and improved postsurgical survival will lead to increased incidence of RGC. Therefore, the indication of endoscopic submucosal dissection (ESD) for RGC is now required, but there have been no reports about this because of the lack of information for RGC. Methods A retrospective review was conducted on 105 patients who underwent completion total gastrectomy (CTG) and 5 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The incidence of lymph node metastasis in early RGC is similar to that of lymph node metastasis in primary early GC[33,34]. Lymph node metastasis of RGC is affected by the current disease stage, not by the initial disease stage.…”
Section: Endoscopic Submucosal Dissection For Gastric Stump Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of lymph node metastasis in early RGC is similar to that of lymph node metastasis in primary early GC[33,34]. Lymph node metastasis of RGC is affected by the current disease stage, not by the initial disease stage.…”
Section: Endoscopic Submucosal Dissection For Gastric Stump Cancermentioning
confidence: 99%
“…However, only one study determined the indication of ESD for RGC. The study found that 17 patients who met the indications of ESD for primary GC had no lymph node metastases after radical gastrectomy of remnant stomach[34].…”
Section: Endoscopic Submucosal Dissection For Gastric Stump Cancermentioning
confidence: 99%
“…Data from 14 studies was pooled in to identify whether the histology of GRC was a risk factor. We analyzed patients who had a well differentiated histology and moderately differentiated histology versus patients who had a poorly differentiated histology and an undifferentiated histology [10,[12][13][14][15]16,18,19,21,24,[27][28][29][30][31]. The statistics showed patients who had a well/moderately differentiated histology were at a lesser risk of being diagnosed with GRC.…”
Section: Histology (Well/moderately Differentiated Versus Poorly Differentiated and Undifferentiated)mentioning
confidence: 99%
“…Moreover, endoscopic submucosal dissection (ESD) of the remnant stomach is technically difficult because of the limited working space, particularly for lesions that involve the suture line or anastomosis, which contains staples and may have severe fibrosis ( 15 ). However, the indications of ESD for primary GC can be applied to RGC ( 16 ). Compared with surgical treatment, ESD is considered a minimally invasive treatment even for early GC in the remnant stomach, based on the reported favorable long-term outcomes ( 15 ).…”
Section: Introductionmentioning
confidence: 99%